2022
DOI: 10.3390/children9060892
|View full text |Cite
|
Sign up to set email alerts
|

Specific Learning Disorder in Children and Adolescents, a Scoping Review on Motor Impairments and Their Potential Impacts

Abstract: Mastering motor skills is important for children to achieve functional mobility and participate in daily activities. Some studies have identified that students with specific learning disorders (SLD) could have impaired motor skills; however, this postulate and the potential impacts remain unclear. The purpose of the scoping review was to evaluate if SLD children have motor impairments and examine the possible factors that could interfere with this assumption. The sub-objective was to investigate the state of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 126 publications
0
9
0
Order By: Relevance
“…A growing body of recent literature supports these findings. For example, a review by Blanchet and Assaiante [ 25 ] cited 36 studies reporting on motor impairments in students with SLD. These studies used a variety of qualitative motor tests, which identified minor to severe levels of motor impairment (fine motor, gross motor, and postural skills) in children with SLD.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of recent literature supports these findings. For example, a review by Blanchet and Assaiante [ 25 ] cited 36 studies reporting on motor impairments in students with SLD. These studies used a variety of qualitative motor tests, which identified minor to severe levels of motor impairment (fine motor, gross motor, and postural skills) in children with SLD.…”
Section: Introductionmentioning
confidence: 99%
“…These studies used a variety of qualitative motor tests, which identified minor to severe levels of motor impairment (fine motor, gross motor, and postural skills) in children with SLD. Children and adolescents with SLDs also showed significant impairments in bilateral coordination, balance, and manual dexterity [ 25 ]. Furthermore, children with SLD displayed poorer performance in timing precision of motor coordination, demonstrated significant deficits in bimanual tasks, and made more sequential errors [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is related, as shown in this study, to the fact that the main research topic is the influence of motor skills on academic performance. The publication carried out by Blanchet et al [ 64 ] in 2022, in which they analyzed how students with specific learning disabilities may have impaired motor skills, stands out. Thus, they concluded that out of the 36 studies analyzed, all reported motor impairments, which can be seen to increase in subjects with ADHD and coordination problems.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, less invasive devices are available (i.e., eye-trackers), which provide the child with a computer interaction community and allow understanding of how children engage with digital technologies, letting novel insights into their visual and cognitive processing [18]. Eye tracking is a method for identifying diagnostic biomarkers with evidence in children with ASD [19][20][21], ADHD [22][23][24][25], ID [26][27][28], SLD [29,30], and CD [24,27]. The role of the autonomic nervous system has earned consideration for many types of neurophysiological features of NDs, such as ASD [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%